Generation X, Y, Z: мoral and religious values as the basis for personal orientation (Actual Problems of Psychology in Educational Institutions, 2021)
The article considers the theory of generations of WilliamStrauss and Neil Howe and presents its characteristics. It summarizes theinfluence of political, social and economic changes on the formation ofvalues of certain groups of generations defined by scientists. Presented isthe religious choice of those born in the period from 1965 to 2010. It isestablished that among Generation Y there is a growing number of thosewho do not identify themselves with religious tradition. The differencebetween the values of generations has been established: a high percentageof non-religious representatives in Generations Y and Z. The impact ofreligious values on the difference in their social and personal attitudes,which affect attitudes towards family, work and religion, was proved
Keywords: theory of generations, values of generations, religion, moral values, personality, career